Interventional pain management in dogs with lumbosacral stenosis: preliminary long-term clinical outcomes of combined foraminal and epidural injections with or without pulsed radiofrequency - Medina-Serra, Roger; Laredo, Francisco G.; de Strobel, Francesca; Sanchis-Mora, Sandra; Belda, Eliseo (Frontiers in Veterinary Science, 2026)
IntroductionLumbosacral stenosis is a recognised cause of pain in dogs, often involving disc herniation and foraminal narrowing with associated radiculopathy. In humans, transforaminal injections demonstrate superior outcomes to interlaminar approaches and are frequently combined with pulsed radiofrequency (PRF) at the dorsal root ganglion (DRG) to enhance pain relief. However, their clinical utility in dogs with naturally occurring lumbosacral pain remains unreported.MethodsThis retrospective cohort study evaluated long-term outcomes (capped at 24 months) following a single procedure involving ultrasound- and fluoroscopy-guided foraminal and epidural corticosteroid and local anaesthetic injections, with (PRF; 9 dogs) or without PRF (No-PRF; 9 dogs) at the L7 DRG, in dogs with chronic lumbosacral pain. Outcome measures included clinician-based Lumbosacral Pain (LSPain) Scale scores and caregiver-reported Canine Brief Pain Inventory (CBPI) scores and quality of life (QoL). Clinically relevant improvement was defined as a two-grade reduction in LSPain Scale score and a CBPI decrease of ≥1 point in pain severity and ≥2 points in pain interference. Data were analysed using Fisher’s Exact Test, Wilcoxon signed-rank tests, Mann–Whitney U tests, and generalised linear mixed models in R.ResultsBaseline outcomes did not differ significantly between groups. Pain severity and QoL improved significantly over time within both groups (p < 0.05). Dogs receiving PRF had significantly greater QoL improvement (p = 0.0247). Clinically relevant improvement was achieved in 9/9 of dogs in the PRF group and 5/9 in the No-PRF group. The median duration of clinically relevant improvement was longer in the PRF group [16.4 (2.2–24) months] than in the No-PRF group [8.9 (0 to 24) months], although this difference did not reach statistical significance in the sample size studied.DiscussionThese preliminary findings suggest that image-guided targeted injections, with or without adjunctive PRF, may provide long-term pain alleviation in dogs with lumbosacral stenosis.